Good Corporate Governance Mechanism And Profitability To Corporate Value In The Idx-Listed Property And Real Estate Sector For The Period 2018-2021 - Muhamad Muslih; Jihan Fijria Rahmadhiany (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
A high company value indicates that the company's performance in obtaining profits is done well. Thus, the market's positive response to the company can increase stock prices and can provide welfare for shareholders. This study aims to determine how the influence caused by institutional ownership, independent board of commissioners, audit committees are measured using accounting and financial expertise, and profitability measured using ROA on company value measured using PBV. The population used is the property and real estate sector listed on the IDX in 2018-2019. The sampling technique uses purposive sampling with certain criteria so that the results of 33 companies were obtained, with a total research sample of 132 observational data for 4 years.The data used is secondary data and comes from the annual report and financial statements of property and real estate sector companies listed on the IDX for 2018-2021. The data analysis technique uses regression analysis of panel data processed with Eviews 12 software. The results indicate that simultaneously, institutional ownership, an independent board of commissioners, an audit committee, and profitability have a significant effect on the value of the company. While partially, institutional ownership and audit committees have a significant effect. However, the board of commissioners is independent and profitability does not have a significant effect on the value of the company.